Time-Resolved Measurement of Deformation of Metal Plates Due to High-Velocity Impacts. (2017) - Jannotti, Phillip; Doney, Robert; Schuster, Brian
Abstract: A methodology is presented for analysing the rear surface deformation of metal plates impacted at ordnance velocities to hypervelocities. Ultra-high-speed imaging and Photonic Doppler Velocimetry are used concurrently to provide a real-time, quantitative description of the plate bulge development and morphology. The utility of the described approach is demonstrated through time-resolved terminal ballistic experiments on metal plates impacted by copper spheres at 2200 m/s. The rear surface damage evolution was evaluated for projectile diameter to target thickness ratios of 1 and 2. The impactor diameter was held constant at 6.4 mm and two different plate thicknesses of approximately 3.2 and 6.4 mm were examined. The target materials included rolled homogenous armour (RHA) steel, titanium alloy Ti-6Al-4V, aluminium alloy Al-6061-T6, and magnesium alloy Mg-AZ31B-H24.